Transcriptomic and Proteomic Insights into the Effect of Sterigmatocystin on Aspergillus flavus - Yarong Zhao; Rui Zeng; Peirong Chen; Chulan Huang; Kaihang Xu; Xiaomei Huang; Xu Wang (Journal of Fungi, 2023)
Aspergillus flavus is an important fungus that produces aflatoxins, among which aflatoxin B1 (AFB1) is the most toxic and contaminates food and poses a high risk to human health. AFB1 interacts with another mycotoxin sterigmatocystin (STC), which is also a precursor of AFB1. Herein, we determined the effect of STC on AFB1 by evaluating A. flavus transcriptomic and proteomic profiles in the presence or absence of STC by RNA-seq and isobaric tagging, respectively. Overall, 3377 differentially expressed genes were identified by RNA-seq. These genes were mainly associated with the cellular component organisation and biosynthesis, the synthesis of valine, leucine, and isoleucine, and the synthesis of aflatoxin. Clustered genes responsible for AFB1 biosynthesis exhibited varying degrees of downregulation, and norB expression was completely suppressed in the experimental group. During proteomic analysis, 331 genes were differentially expressed in response to STC. These differentially expressed proteins were associated with cell parts and catalytic and antioxidant activities. Differentially expressed proteins predominantly participated in metabolic pathways associated with aflatoxin biosynthesis, glycolysis/gluconeogenesis, glutathione metabolism, and carbon metabolism. Notably, the upregulated and downregulated enzymes in carbohydrate and glutathione metabolisms may serve as potential gateways for inhibiting aflatoxin biosynthesis. Moreover, twelve proteins including seven downregulated ones involved in aflatoxin biosynthesis were identified; among them, AflG was the most downregulated, suggesting that it may be the key enzyme responsible for inhibiting aflatoxin synthesis. These findings provide novel insights into A. flavus control and the mechanisms regulating mycotoxin production.